Acute Cerebrovascular Accident, Renal Failure, and Thrombotic Microangiopathy in a 27‐Year‐Old Male With Malignant Hypertension - Tatiana Gusan; Angelina Hong; Sarah Kaufman; Luis Santiago; Nathan Zaher (Clinical Case Reports)
ABSTRACT Hypertensive emergency is an acute, significant elevation of blood pressure accompanied by end‐organ damage. We present a case of a 27‐year‐old gentleman who acquired multiple complications of hypertensive emergency, including renal failure and microangiopathy. This highlights the diverse complications of hypertensive emergency and reviews guideline‐based recommendations for management.